2021
DOI: 10.32604/or.2022.025262
|View full text |Cite
|
Sign up to set email alerts
|

GABPB1-AS1 acts as a tumor suppressor and inhibits non-small cell lung cancer progression by targeting miRNA-566/F-box protein 47

Abstract: It has been certified that GABPB1-AS1 is aberrantly expressed and plays as a vital role in some kinds of cancers.However, its expression pattern and functions in non-small cell lung cancer (NSCLC) are still largely unknown. This study aims to assess GABPB1-AS1 expression and biological roles in NSCLC. The expression of GABPB1-AS1 was detected in NSCLC specimens and adjacent normal specimens. CCK8 and Transwell assays were performed to evaluate the effects of GABPB1-AS1 on NSCLC cell proliferation, migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In lung carcinomas, differential expression of lncRNAs has been observed depending on the cancer type. Representative cases are SLC9A3-AS1, reported upregulated; LINC01554 and GABPB1 reported downregulated in NSCLC tissues [166][167][168], while RBPMS-AS1 expression was found to be diminished in lung adenocarcinoma [169]. Other studies have shown the reduced expression of LINC00294 in colorectal carcinoma tissues [170], while SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2, AC026362.1 were found to be downregulated in colon cancer cell lines [171].…”
Section: Discussionmentioning
confidence: 96%

miRNAs as Interconnectors between Obesity and Cancer

González-Sánchez,
Granados-López,
López-Hernández
et al. 2024
ncRNA
“…In lung carcinomas, differential expression of lncRNAs has been observed depending on the cancer type. Representative cases are SLC9A3-AS1, reported upregulated; LINC01554 and GABPB1 reported downregulated in NSCLC tissues [166][167][168], while RBPMS-AS1 expression was found to be diminished in lung adenocarcinoma [169]. Other studies have shown the reduced expression of LINC00294 in colorectal carcinoma tissues [170], while SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2, AC026362.1 were found to be downregulated in colon cancer cell lines [171].…”
Section: Discussionmentioning
confidence: 96%

miRNAs as Interconnectors between Obesity and Cancer

González-Sánchez,
Granados-López,
López-Hernández
et al. 2024
ncRNA
“…GABPB1-AS1 is negatively associated with response and is a long non-coding RNA (lncRNA) that regulates GABPB1. Upregulation of GABPB1-AS1 can eventually suppress the cellular antioxidant capacity and has been found to serve as a potential biomarker in prostate cancer (56)(57)(58). ANKRD49 is positively associated with response, and is responsible for upregulating cell proliferation (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignant tumors globally, exhibiting the highest morbidity rate in recent years 31 , 61 . It encompasses two primary classifications: nonsmall-cell lung cancer (NSCLC), constituting ~85% of cases, and small-cell lung cancer (SCLC), accounting for ~15% of cases 62 , 63 . Lung adenocarcinoma (LUAD) is the most common histological variety among NSCLC subtypes, accounting for about 60% of cases 64 .…”
Section: Role Of Ska3 In Human Cancermentioning
confidence: 99%